School-House Relationships on Different Stages of Children and Teenagers (Youth) Development - Bednarska, Małgorzata (Pedagogika, 2014)
The school-house relationships have great impact on the quality of the educational process. This article is to draw an attention to those relationships, taking into consideration particularly different relations between the teacher and the parent regarding the stage of development of the student, who is the subject of this issue. It seems that the awareness of parents and teachers of the subject matter of this relationship, on what they should focus, especially what tasks they should perform for the child’s sake and his well being, can significantly improve not only school-house relationships, but above all things, it can generally improve the situation of the child at school which he or she attends.